Resistance induced by circular vegetation patch - Hui, Cai Ling (2017)
Vegetation patches are frequently found in river channels. Besides being able to affect aquatic environments biologically and environmentally, they also impose a greater resistance to the channel flow. Although there have been many studies established on the drag induced by a single cylinder and a group of uniformly distributed cylindrical rods, the understanding of the drag induced by a porous vegetation patch remains unclear. A few studies have been conducted on this subject but the results are still preliminary. Hence, this study aims to investigate the drag induced by vegetation patches of varying porosities and the flow structure around these patches.